Commodification of Ḥajj Rituals amongst Banjarese Pilgrims - Raihani, Raihani; Noor, Irfan; Supriansyah, Supriansyah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
This paper is drawn from a larger study of Banjarese experiences in performing ḥajj or pilgrimage to Saudi Arabia. This phenomenological study employed in-depth interviews with about 50 informants in two different areas where Banjarese populations are concentrated, i.e. South Kalimantan and Indragiri Hilir. The theme of the commodification of rituals including ojek ḥajar aswad and badal haji emerged from the comprehensive data analysis. In theory, commodification refers to the practice to turn something into a commodity. In the experiences of some Banjarese pilgrims, commodified rituals have the importance of both spiritual enhancement and social pride, even though these practices sometimes involve cheating and manipulation from the side of the service providers. So, not only do ḥajj rituals provide sacred experiences for the pilgrims, but also an opportunity for some to make profits from them even through unethical or illegal conduct.